Development of Teaching Module Using the Problem-Based Learning Model Based on Wadai Banjar Ethnomathematics in the Topic of Linear Equation - Shafitri Ardiana; Noor Fajriah; Juhairiah Juhairiah (Universitas Maritim Raja Ali Haji, 2023)
Many students need help to understand linear equation material and obtain low math scores. One of the efforts to overcome this was to research and produce a teaching module using a Problem-Based Learning model based on Wadai Banjar's ethnomathematics material of linear equations that is valid, practical, and effective for the learning. The type of research used is the type of 4-D model development research. The data collection technique used a validation sheet by two validators, a practicality questionnaire filled out by a math teacher and 8 students with various abilities, and a learning achievement test for 27 class VII C students of SMP Negeri 18 Banjarmasin. There are 3 analyses conducted in this study: validity, practicality, and effectiveness test analysis. The results showed an average score of 3,58 was obtained from the validator in the very valid category, an average score from the questionnaire was 3,23 in the practical category, and 66,67% of students obtained an evaluation test score above the average score in the effective category.